Subcutaneous histiocytoid Sweet's syndrome in a patient with myelodysplastic syndrome and acute myeloblastic leukemia. (7th March 2014) - Srisuttiyakorn, Chutika; Reeve, Jennifer; Reddy, Swapna; Imaeda, Suguru; Lazova, Rossitza
<x xml:space="preserve">Abstract</x> Subcutaneous histiocytoid Sweet's syndrome is a rare variant of histiocytoid Sweet's syndrome (SS). We present a 68‐year‐old woman with subcutaneous histiocytoid SS in association with refractory myelodysplastic syndrome transformed to acute myeloblastic leukemia (AML), status post induction chemotherapy and with persistent blasts (50%) in the bone marrow and blood, accompanied with neutropenia. The patient presented to the emergency room with fever and altered mental status. Clinical examination revealed approximately 20 scattered 0.5–2 cm, pink to pink‐purple non‐tender firm nodules on the legs and left arm. The differential diagnosis included Sweet's syndrome (deep), leukemia cutis, infection, polyarteritis nodosa and erythema nodosum. Histopathologic examination of a biopsy from the left arm revealed a nodular infiltrate of neutrophils and histiocytoid mononuclear cells solely in the lobular compartment of the subcutaneous fat with focal areas of necrosis. Most cells in the infiltrate labeled with myeloperoxidase (MPO) including the histiocytoid cells. The cells were negative for CD34 and CD117. All special stains for microorganisms were negative. A diagnosis of subcutaneous histiocytoid SS was made. A subcutaneous histiocytoid SS should be suspected when a neutrophilic/histiocytoid panniculitis, occurring in the setting of myeloid disorders, is encountered and after exclusion of an infectious process and leukemia cutis.